Crescimento epitaxial e caracterização de filmes finos: óxidos condutores e ferroelétricos preparados por deposição de solução química - Capeli, Regina Aparecida [UNESP] (2016)
In this paper the citrates polymerized solutions with high chemical homogeneity of compounds of Perovskite structure composite systems Pb0,76Ca0,24TiO3(PCT24) e LaNiO3(LNO) were applied to prepare thin films textured/epitaxial. It was made the growth of PCT24 on LNO thin films deposited on single crystal substrates such as on LaAlO3 (100), LaAlO3 (001) and LaAlO3 (111) for verification of texturing and its preferred orientation. The dependence of the dielectric/ferroelectric and electronic transport properties with respect to texturing properties were evaluated for the formation of electronic devices for thin films PCT24 and LNO, respectively. It was also performed a comparative study of electrical properties of thin films with LNO base electrode and platinum. The effects of the arrangement and orientation of the ferroelectric domains as well as texturing, the electrical properties of ferroelectric films were evaluated and correlated with the crystallographic characteristics, microstructure and stoichiometric (chemical composition) of materials. Therefore, the possibility of obtaining ferroelectric this material opens a new front of research and perspectives with respect to the same job in different types of electronic devices.